RE: American Dream (Oz, 1993)
Los Angeles has seen unprecedented and rampant exploitation by hegemonous political and economic forces which dissolve the public realm of the city into a seamless horizontal experience of bankrupt formal gestures devoid of value either urbanistically or architecturally.